Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1093/ijnp/pyu017
|View full text |Cite
|
Sign up to set email alerts
|

Bupropion Increases Selection of High Effort Activity in Rats Tested on a Progressive Ratio/Chow Feeding Choice Procedure: Implications for Treatment of Effort-Related Motivational Symptoms

Abstract: Background:Depression and related disorders are characterized by deficits in behavioral activation, exertion of effort, and other psychomotor/motivational dysfunctions. Depressed patients show alterations in effort-related decision making and a bias towards selection of low effort activities. It has been suggested that animal tests of effort-related decision making could be useful as models of motivational dysfunctions seen in psychopathology.Methods:Because clinical studies have suggested that inhibition of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
93
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 78 publications
(156 reference statements)
10
93
1
Order By: Relevance
“…This work was undertaken to focus on effort-related functions that may be highly relevant for understanding some of the motivational symptoms of depression and other disorders (Nunes et al, 2013a,b;Randall et al, 2014Randall et al, , 2015Treadway et al, 2012;Yohn et al, 2015). Rodent tests of effort-related dysfunction are likely to reflect a component of depression rather than a global measure, and possibly represent models of motivational symptoms that cross multiple diagnostic categories, rather than a model of a specific disorder .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work was undertaken to focus on effort-related functions that may be highly relevant for understanding some of the motivational symptoms of depression and other disorders (Nunes et al, 2013a,b;Randall et al, 2014Randall et al, , 2015Treadway et al, 2012;Yohn et al, 2015). Rodent tests of effort-related dysfunction are likely to reflect a component of depression rather than a global measure, and possibly represent models of motivational symptoms that cross multiple diagnostic categories, rather than a model of a specific disorder .…”
Section: Discussionmentioning
confidence: 99%
“…Bupropion, a catecholamine reuptake blocker that elevates extracellular DA and norepinephrine (NE; Hudson et al, 2012;Randall et al, 2015), has been shown to reverse the effort related effects of TBZ (Nunes et al, 2013;Randall et al, 2014;Yohn et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Disruptions of effort-related decision making can be induced by several manipulations associated with depression, including stress (Shafiei et al, 2012), stimulation of muscarinic acetylcholine receptors in NAcc (Nunes et al, 2013a), and administration of the pro-inflammatory cytokine interleukin 1-β (Nunes et al, 2014). Recent studies also characterized the effort-related effects of the vesicular monoamine transport (VMAT) inhibitor tetrabenazine (Nunes et al, 2013b;Randall et al, 2014). Tetrabenazine produces depressive symptoms in humans (Guay, 2010;Frank, 2009Frank, , 2010, and because of its selective inhibition of VMAT-2, it preferentially depletes striatal DA (Pettibone et al, 1984).…”
Section: Conceptual Background: Motivationmentioning
confidence: 99%
“…Tetrabenazine produces depressive symptoms in humans (Guay, 2010;Frank, 2009Frank, , 2010, and because of its selective inhibition of VMAT-2, it preferentially depletes striatal DA (Pettibone et al, 1984). Rats were tested on concurrent lever pressing/chow feeding choice tasks, and tetrabenazine shifted response choice from the high effort response (lever pressing) to the low effort alternative (approach and consumption of chow; Nunes et al, 2013b;Randall et al, 2014). Yet despite these effort-related impairments, tetrabenazine did not alter food intake or preference in parallel free-feeding choice studies.…”
Section: Conceptual Background: Motivationmentioning
confidence: 99%
“…The doses employed in the current research were selected on the basis of previous studies about the effects of bupropion in NMRI mice (Carrasco et al, 2004(Carrasco et al, , 2013Gomez et al, 2009a,b;Redolat et al, 2005a,b) and are in the range of doses habitually used to assess behavioral effects of bupropion in rodents (Biała and Kruk, 2009;Lipina and Roder, 2010;Randall et al, 2014).…”
Section: Drugsmentioning
confidence: 99%